Dexmedetomidine Ameliorates the Neurotoxicity of Sevoflurane on the Immature Brain Through the BMP/SMAD Signaling Pathway - Shan, Yangyang; Yang, Fan; Tang, Zhiyin; Bi, Congjie; Sun, Shiwei; Zhang, Yongfang; Liu, Hongtao (Frontiers in Neuroscience, 2018)
Abstract The effect of general anesthetics on the developing brain has attracted much attention because numerous studies have demonstrated that general anesthetics damage the nervous system to an extent. Dexmedetomidine (Dex) exhibits a certain neuroprotective effect, but the mechanism is obscure. In our study, pregnant rats on gestation day 20 (G20) were exposed to 3% sevoflurane for 2 h or 4 h, and hippocampal neuronal apoptosis was detected in the brains of the offspring. Different doses of Dex were intraperitoneally injected before sevoflurane anesthesia to investigate whether Dex could repress sevoflurane-induced neurological impairment. As an antagonist of the BMP receptor, DMH1 was co-administered with sevoflurane plus Dex to investigate whether BMP/SMAD is associated with the neuroprotective effects of Dex. The results showed that sevoflurane anesthesia for 4 h during the third trimester activated apoptosis and axonal injury, as manifested by an increase in caspase-3, amyloid precursorprotein (APP) and p-CRMP-2 and a decrease of CRMP-2 in postnatal rat hippocampus; this effect further impaired long-term learning and memory ability. These damaging effects of sevoflurane could be mitigated by Dex at 10 μg/kg and 20μg/kg but not at 5μg/kg, and DMH1 reversed the neuroprotective effect of Dex. Our results indicated that prenatal exposure to 3% sevoflurane for 4 h increased apoptosis and axonal injury, even accompanied by long-term learning and memory dysfunction in the offspring rats. Dex dose-dependently reduces sevoflurane- anesthesia-induced the neurotoxicity by activating the BMP/SMAD signaling pathway.